Necrosis of the Ventral Penile Skin Flap: A Complication of Hypospadias Surgery in Children - Bakal, Unal; Abes, Musa; Sarac, Mehmet (Hindawi Ltd, 2015)
Objectives. To review cases of hypospadias that were repaired with TIPU method and consequently resulted in the necrosis of ventral penile skin flaps. Methods. Eighty-three patients with hypospadias underwent TIPU procedure by two surgeons. Neourethra in all patients was covered with dartos flap prepared from the preputium or penile shaft. In cases where ventral skin could not be covered primarily, closure was ensured by using preputial Ombredanne or Byars' flaps to repair ventral defects. Results. The median age of patients was 4 years. Twenty-five (30.12%) patients that underwent hypospadias repair had urethral opening at the coronal level, 33 (39.75%) at the distal penis, 10 (12.04%) at the midpenis, and 15 (18.07%) at the proximal penis. The ventral skin defect could not be primarily covered in 10 patients with penile shaft hypospadias. Consequently, Byars' method was used in 8 of these patients to cover the defect and the Ombredanne method was used in the remaining 2. Ventral skin flap necrosis developed in 5 patients (4 Byars and 1 Ombredanne). It was medically treated in 4 patients. Urethral fistula developed in the other patient whose necrosis was deeper. The mean hospital stay was 7 days for patients without necrosis, and 14 for those with necrosis. Conclusion. We are of the opinion that dartos flaps used in the TIPU method in order to cover neourethra and decrease the incidence of fistula development lead to necrosis in the Ombredanne or Byars' flaps by causing low blood supply to the preputium and thus extend hospital stay.
Keywords: Plate